A new species of the rare nematode genus Rostrulium Siddiqi, 1995 (Nematoda: Dorylaimida: Tylencholaimidae) from India - Islam, Md. Niraul; Imran, Zarrin; Ahmad, Wasim (Zootaxa, 2019)
Rostrulium indicum sp. n. is described and illustrated from Western Ghats, India. The new species is characterized by having a 2.1 mm long body; lip region offset by slight constriction; odontostyle 17.5 µm and odontophore 18 µm long, guiding ring single; pharynx with slender anterior part which expands gradually into the cylindrical basal bulb occupying about 30% of total neck length; female genital system didelphic-amphidelphic, transverse vulva, short rounded conoid tail and male with 40 µm long spicules, lateral guiding pieces and three spaced ventromedian supplements. This is the first report of this rare genus since its original description from Cameroon.